Hypovitaminosis D in children with type 1 diabetes mellitus and its influence on biochemical and densitometric parameters - Vojtková, Jarmila; Ciljaková, Miriam; Vojarová, Lenka; Janíková, Katarína; Michnová, Zuzana; Sagiová, Veronika (Acta medica (Hradec Kralove), 2012)
The aim of the study was to establish the frequency of hypovitaminosis D in children with type 1 diabetes mellitus (T1D), its influence on biochemical and densitometric parameters and the relation to diabetic nephropathy. 58 children with T1D at the age 9-19 years were enrolled to the study. Vitamin D concentration less than 30 ng/ml was considered as insufficient. 37 children (63.79%) had vitamin D level under 30 ng/ml, from these 19 subjects (32.7%) had vitamin D level under 20 ng/ml and 2 subjects (3.44%) under 10 ng/ml. Children with vitamin D deficiency had significantly lower magnesium concentration and lower Z score of lumbar spine (-1.34 +/- 1.24 vs. -.030 +/- 1.21, p = 0.01) compared to diabetics with sufficient vitamin D concentration. No significant difference was found in parameters calcium, phosphorus or glycosylated hemoglobin. Patients with diabetic nephropathy (n = 18) showed no significant difference in vitamin D, glycosylated hemoglobin or Z score of lumbar spine compared to the patients without nephropathy (n = 40). Subjects with nephropathy had significantly longer diabetes duration, significantly higher cholesterol and triacylglycerol concentration. In our cohort of patients nearly two thirds of children had insufficient vitamin D concentration what supports the need to monitor and eventually supplement vitamin D in T1D subjects.
Keywords: Diabetic Nephropathies; Vitamin D Deficiency; diabetické nefropatie; diabetes mellitus 1. typu; mladiství; vápník; Glycated Hemoglobin A; mužské pohlaví; nedostatek vitaminu D; mladý dospělý; dítě; Child; Calcium; Diabetes Mellitus, Type 1; Young Adult; ženské pohlaví; Humans; Glycated Hemoglobin; Bone Density; glykovaný hemoglobin; kostní denzita; fosfor; Female; Adolescent; lidé; Male; Phosphorus